Severe Postcoital Bleeding From a Uterine Artery Pseudoaneurysm 4 Months After Cesarean Delivery. Issue 3 (September 2015) - Chummun, Kushal; Kroon, Nicolette; Flannelly, Grainne; Brophy, David
Abstract : BACKGROUND: Uterine artery pseudoaneurysm is considered a rare complication of gynecologic and obstetric procedures. The delayed diagnosis of this condition may result in life-threatening hemorrhage. CASE: A 34-year-old woman underwent an urgent cesarean delivery for labor dystocia. The procedure was complicated with hemorrhage from the uterine incision angles requiring extra hemostatic suture. She presented with secondary postpartum hemorrhage on day 14 and again with life-threatening postcoital vaginal bleeding 4 months after cesarean delivery. Magnetic resonance imaging and angiography revealed a uterine artery Pseudoaneurysm, which was treated with uterine artery embolization. CONCLUSION: Uterine artery pseudoaneurysm should be considered as a differential diagnosis in patients presenting with postpartum hemorrhage, especially if bleeding is significant and recurrent, particularly after an operative delivery. The diagnosis of a pseudoaneurysm can be made by color Doppler ultrasonography, computed tomography, magnetic resonance imaging, and angiography. Abstract : Uterine artery pseudoaneurysm should be considered and investigated with Doppler ultrasonography or computed tomography in all cases of massive vaginal bleeding occurring after obstetric and gynecologic procedures.